Bicyclic Basic Merbarone Analogues as Antiproliferative Agents - Andrea Spallarossa; Matteo Lusardi; Chiara Caneva; Aldo Profumo; Camillo Rosano; Marco Ponassi (Molecules, 2021)
Pyrimido-pyrimidine derivatives have been developed as rigid merbarone analogues. In a previous study, these compounds showed potent antiproliferative activity and efficiently inhibited topoisomerase IIα. To further extend the structure–activity relationships on pyrimido-pyrimidines, a novel series of analogues was synthesized by a two-step procedure. Analogues 3–6 bear small alky groups at positions 1 and 3 of the pyrimido-pyrimidine scaffold whereas at position 6a (4-chloro)phenyl substituent was inserted. The basic side chains introduced at position 7 were selected on the basis of the previously developed structure–activity relationships. The antiproliferative activity of the novel compounds proved to be affected by both the nature of the basic side chain and the substituents on the pyrimido-pyrimidine moiety. Derivatives 5d and 5e were identified as the most promising molecules still showing reduced antiproliferative activity in comparison with the previously prepared pyrimido-pyrimidine analogues. In topoisomerase IIα-5d docking complex, the ligand would poorly interact with the enzyme and assume a different orientation in comparison with 1d bioactive conformation.